2009
DOI: 10.1353/cpr.0.0052
|View full text |Cite
|
Sign up to set email alerts
|

Building Community Participatory Research Coalitions from the Ground Up: The Philadelphia Area Research Community Coalition

Abstract: Building a CBPR coalition from the ground up involving organizations of diverse size and at various stages of development presents unique challenges that can be overcome with committed leadership, clear governance principles, and appropriate infrastructure. Engagement in community-based research during the early stages, while still developing trust, structure, and governance procedures can be accomplished as long as training of all partners is conducted and the trust building is not ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Partners who are committed to the partnership and its work and share power, risk, responsibility, and accountability create the atmosphere and support for positive collaborations that facilitate long-term partnerships (Baquet, Bromwell, Hall, & Frego., 2013; Ferré, Jones, Norris, & Rowley, 2010; Pivik & Goelman, 2011). Individual partner characteristics identified also indicated that they be representative and appropriate to the partnership’s work such that they bring their unique skills, expertise, and perspectives to all aspects of the partnership’s research (Ferré et al, 2010; Goold et al, 2016; Johnson et al, 2009; Pivik & Goelman, 2011). In addition, such partners need to be able to make decisions on behalf of the organizations they represent (Baquet, 2012; Hicks et al, 2012) and actively engage at all levels of partnership work to ensure that community needs and goals are prioritized (Chino, 2012; Goodman et al, 2017; Morales et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Partners who are committed to the partnership and its work and share power, risk, responsibility, and accountability create the atmosphere and support for positive collaborations that facilitate long-term partnerships (Baquet, Bromwell, Hall, & Frego., 2013; Ferré, Jones, Norris, & Rowley, 2010; Pivik & Goelman, 2011). Individual partner characteristics identified also indicated that they be representative and appropriate to the partnership’s work such that they bring their unique skills, expertise, and perspectives to all aspects of the partnership’s research (Ferré et al, 2010; Goold et al, 2016; Johnson et al, 2009; Pivik & Goelman, 2011). In addition, such partners need to be able to make decisions on behalf of the organizations they represent (Baquet, 2012; Hicks et al, 2012) and actively engage at all levels of partnership work to ensure that community needs and goals are prioritized (Chino, 2012; Goodman et al, 2017; Morales et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Coalition or partnership development is context dependent (Kegler, Rigler, & Honeycutt, 2010). Consequently, we recommend that each PH-PBRN examine the CBPR literature, which is replete with tools, examples, and lessons learned for partnership development from which they may benefit (Andrews, Cox, Newman, & Meadows, 2011; Becker, Israel, & Allen, 2005; Fawcett, Schultz, Watson-Thompson, Fox, & Bremby, 2010; Israel, Lichtenstein, et al, 2001; Johnson et al, 2009; KU Work Group for Community Health and Development, 2016; Lewis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…8 PARCC, organized in 2005, is comprised of about 20 community organizations conducting health related programs in Wests/Southwest Philadelphia, representing many different stakeholders; grassroots, school-based, faith, academic, private nonprofits, and government. PARCC was organized out of the expressed interests of communities in the West/Southwest Philadelphia area to become partners with academic researchers in CBPR.…”
Section: Partnerships In the Pcvpcmentioning
confidence: 99%